Mutation update for the GPC3 gene involved in Simpson‐Golabi‐Behmel syndrome and review of the literature. Issue 6 (24th April 2018) - Vuillaume, Marie‐Laure; Moizard, Marie‐Pierre; Rossignol, Sylvie; Cottereau, Edouard; Vonwill, Sandrine; Alessandri, Jean‐Luc; Busa, Tiffany; Colin, Estelle; Gérard, Marion; Giuliano, Fabienne; Lambert, Laetitia; Lefevre, Mathilde; et al.
Abstract: Simpson‐Golabi‐Behmel syndrome (SGBS) is an X‐linked multiple congenital anomalies and overgrowth syndrome caused by a defect in the glypican‐3 gene ( GPC3 ). Until now, GPC3 mutations have been reported in isolated cases or small series and the global genotypic spectrum of these mutations has never been delineated. In this study, we review the 57 previously described GPC3 mutations and significantly expand this mutational spectrum with the description of 29 novel mutations. Compiling our data and those of the literature, we provide an overview of 86 distinct GPC3 mutations identified in 120 unrelated families, ranging from single nucleotide variations to complex genomic rearrangements and dispersed throughout the entire coding region of GPC3 . The vast majority of them are deletions or truncating mutations (frameshift, nonsense mutations) predicted to result in a loss‐of‐function. Missense mutations are rare and the two which were functionally characterized, impaired GPC3 function by preventing GPC3 cleavage and cell surface addressing respectively. This report by describing for the first time the wide mutational spectrum of GPC3 could help clinicians and geneticists in interpreting GPC3 variants identified incidentally by high‐throughput sequencing technologies and also reinforces the need for functional validation of non‐truncating mutations (missense, in frame mutations, duplications). Abstract : We provide, for the first time, an overview of the mutational spectrum of GPC3, the gene involved in Simpson‐Golabi‐Behmel syndrome, an X‐linked multiple congenital anomalies and overgrowth syndrome, through the description of the 86 distinct mutations, ranging from single nucleotide variations to complex genomic rearrangements, identified until now. The vast majority of these mutations are deletions or truncating mutations (frameshift, nonsense mutations) predicted to result in a loss of function, whereas missense mutations are rare and need functional validation.